Antibacterial Activity of Coconut Yoghurt against Streptococcus mutans in Vitro - Isnaini, Ananda Amalia; Trimulyono, Guntur (LenteraBio : Berkala Ilmiah Biologi, 2024)
Streptococcus mutans is one of the bacteria that causes dental caries. Treatment efforts by using antibiotics, but excessive use of antibiotics that do not comply with guidelines can cause resistance. Coconut yoghurt (cocoghurt) is a yoghurt product made from coconut milk fermented with the help of lactic acid bacteria and contains antibacterial compounds. This study aims to determine the antibacterial activity of cocoghurt made by varying the composition ratio of the bacteria Lactobacillus bulgaricus and Streptococcus thermophilus (2:1, 1:1, and 1:2). The research was carried out in several stages, namely rejuvenation and making bacterial suspension, making coconut milk, making a starter, making cocoghurt, and antibacterial test used the well-diffusion method. The test results were analyzed using the Kolmogorov-Smirnov test, the One-Way ANOVA test, and the Duncan test. Based on the statistical analysis, cocoghurt made with variations in the composition of starter bacteria affected the growth of S. mutans. The treatment group showed a significant difference from the control group but did not indicate a significant difference from the other treatment groups. The best composition ratio of starter bacteria in making cocoghurt in inhibiting S. mutans is a ratio of 1:2 with an inhibitory zone diameter of 5.20 ± 1.72 mm. This research proves that cocoghurt can inhibit the growth of S. mutans, so expected it can be used as an alternative in the medication and prevention of dental caries.